Sources of Sampling Bias in Sex Studies. - Benson, Purnell H.; Bentley, Evelyn (Public Opinion Quarterly)
This article identifies the sources of sampling bias in sex studies. It has been pointed out that the sampling procedures employed by A.C. Kinsey may have introduced biases into his findings. These procedures provide for the use of respondents willing to be interviewed who are members of organizations included as sampling units. In the Ernest W. Burgess-Paul Wallin study, data were obtained which permit the influence of voluntarism upon findings concerning marital adjustment to be examined. Burgess and Wallin also collected data, which permit tests to be made of whether voluntarism is a source of sampling bias in the enumeration of sexual activities, and of whether organizational membership affects findings concerning sexual activities. The data were obtained from 1000 engaged couples willing to fill out questionnaires, with an intensive follow up study being made of 666 of the couples after they had been married for several years. For the most part, the couples were college educated, urban, middle class subjects.